Biodegradation of Petroleum Hydrocarbons in Soil - MR Mehrasbi; B Haghighi; M Shariat; S Naseri; K Naddafi (Tehran University of Medical Sciences, 2003)
Biodegradation of petroleum hydrocarbons (20 g/kg dw soil) was investigated in 3 media, differing in the kind of petroleum fractions. In the laboratory experiments, during 5 months, the activities of petroleum hydrocarbon-degrading microorganisms and dehydrogenase activity of soil was determined. Gas chromatographic analysis showed the biological decontaminations for gas oil, kerosene and synthetic mixture (gas oil, kerosene and furnace oil) are 60 %, 36 % and 55 %, respectively. Dehydrogenase activity which was assessed by TTC technique, correlated significantly positive with the numbers of microorganisms. The Spearman rank correlation coefficients(r) in contaminated soils with gas oil, kerosene and synthetic mixture were 0.79, 0.80 and 0.69, respectively.